Pengembangan Modul Program Linier Berbasis Pembelajaran Mandiri - Mardia, Ainun; Sundara, Vinny Yuliani (Edumatica : Jurnal Pendidikan Matematika, 2020)
Modules are teaching materials that are often used in lectures. Modules can be used independently by students and are not spared by the guidance of lecturers in the course. The purpose of this research is to develop a linear program module based on independent learning by using the following steps: defining, designing, and developing. The linear learning module based on independent learning is validated by media experts, material experts, and linguists. Measurement of the validity of this module with a validation sheet and practicality in the value of the questionnaire given to students. Module development is explained qualitatively while data from the validation sheet and questionnaire are analyzed quantitatively. The results of the validation of the presentation, content, and language by media experts, material experts, and linguists obtained values ​​for presentation validation of 4.00, content validation obtained a value of 3.6, and language validation obtained a value of 3.83 which means that the module content the independent learning based linear program is valid in terms of presentation, content, and language. While the analysis of the practicalisation questionnaire by students obtained a value of 90% that the linear program module is based on independent learning in the practical category. Practicality can be seen from attractive and systematic appearance, using problem solving steps, clarity of material content presented, ease of use of modules, and words used are easy to understand according to characteristics college student.